2013
DOI: 10.4209/aaqr.2012.11.0315
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Arsenic Deposition in Chiayi County in Southern Taiwan

Abstract: Although arsenic contamination of underground water in southern Taiwan is well known, few studies examine atmospheric arsenic deposition in this area, which might be the major source of such pollution to the soil, water, and even underground water. This research focused on the atmospheric arsenic concentration, dry and wet depositions, and the As distribution around Chiayi County, located in the south of Taiwan. Eight sampling sites are used, both upwind and downwind of an area with heavy industrial and human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
4
2
Order By: Relevance
“…The majority of the annual As deposition at both sites was contributed to by wet deposition (GZ: 78.85%, DH: 84.05%). The percentages were significantly higher than the results studied in Chialy, South Taiwan, 48 North China, 51 and the cities across Japan. 49,53 Moreover, dry deposition is even found to be the more important mechanism in North China 51 and most cities in Japan.…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…The majority of the annual As deposition at both sites was contributed to by wet deposition (GZ: 78.85%, DH: 84.05%). The percentages were significantly higher than the results studied in Chialy, South Taiwan, 48 North China, 51 and the cities across Japan. 49,53 Moreover, dry deposition is even found to be the more important mechanism in North China 51 and most cities in Japan.…”
Section: Resultscontrasting
confidence: 81%
“…No significant difference ( p > 0.05) was observed between two sites. In comparison with other studies around the world, the total deposition fluxes in the present study were extraordinarily higher than those reported in the US, Europe, and Australia and comparable to the Yangtze River Delta (YRD) region, Taiwan, and Japan; whereas, they were lower than the Shanxi Basin, the largest coal basin in China, as well as the Beijing-Tianjin-Hebei region in China, where it is one of the regions with the highest atmospheric As concentration around the world , (SI Table S2).…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…In the rural area of China, the average As content in the atmosphere was 47.66 mg kg −1 , while the dry deposition flux of As was 1.7 mg m −2 a −1 16 . The average atmospheric dry and wet deposition fluxes of As ranged from 0.41 to 1.93 mg m −2 a −1 and 0.14 to 4.97 mg m −2 a −1 in the Chiayi County in Southern Taiwan, respectively 17 . A previous study showed that anthropogenic As from atmospheric deposition led to a greater accumulation of As in the O horizons of Haplocryod and Cryorthent in northern Sweden 8 .…”
Section: Resultsmentioning
confidence: 99%
“…However, due to disagreements in correlation coefficients in various regions, it was inferred that other factors such as aerosol vertical structure, humidification, spatial and temporal states, and meteorological conditions have effects on AOD-PM relationship (Chu et al, 2003;Wang, 2003;Paciorek and Liu, 2010). Based on this, complex statistical methods, such as mixed effect models, general additives models (GAM), Bayesian hierarchical models and geographically weighted regression (GWR), together with ground or model based ancillary data, have been used to study AOD-PM (Liu et al, 2009;Tian and Chen, 2010;Lee et al, 2011;Lin et al, 2013). The feasibility of these complex models, generally require more ancillary data, has not been validated, especially in developing countries (Liu, 2013).…”
Section: Introductionmentioning
confidence: 99%